Incorporation Of Bisphosphonates In Surface Of The Ti30Ta After Biomimetic Treatment - Alves Claro, Ana Paula Rosifini [UNESP]; Carvalho, Luciana Maria Ferreira; Rezende, Maria Cristina Rosifini Alves [UNESP] (My University, 2013)
The purpose of this study was the incorporation of the bisphosphonate (sodium alendronate) in surface of the Ti30Ta alloy after biomimetic treatment. In vitro and in vivo studies were made for to evaluate its incorporation and enhance of the osseointegration.